NLRP11 is required for canonical NLRP3 and non-canonical inflammasome activation during human macrophage infection with mycobacteria - Mateusz Szczerba; Akshaya Ganesh; María Luisa Gil-Marqués; Volker Briken; Marcia B. Goldberg (mBio)
ABSTRACT The NLRP11 protein is only expressed in primates and participates in the activation of the canonical NLRP3 and non-canonical NLRP3 inflammasome activation after infection with gram-negative bacteria. Here, we generated a series of defined NLRP11 deletion mutants to further analyze the role of NLRP11 in NLRP3 inflammasome activation. Like the complete NLRP11 deletion mutant (NLRP11−/−), the NLRP11 mutant lacking the NAIP, C2TA, HET-E, and TP1 (NACHT) and leucine-rich repeat (LRR) domains (NLRP11∆N_LRR) showed reduced activation of the canonical NLRP3 inflammasome, whereas a pyrin domain mutant (NLRP11∆PYD) had no effect on NLRP3 activation. The NLRP11−/− and NLRP11∆N_LRR mutants, but not the NLRP11∆PYD mutant, also displayed reduced activation of caspase-4 during infection with the intracytosolic, gram-negative pathogen Shigella flexneri. We found that the human-adapted, acid-fast pathogen Mycobacterium tuberculosis and the opportunistic pathogen Mycobacterium kansasii both activate the non-canonical NLRP11 inflammasome in a caspase-4/caspase-5-dependent pathway. In conclusion, we show that NLRP11 functions in the non-canonical caspase-4/caspase-5 inflammasome activation pathway and the canonical NLRP3 inflammasome pathway and that NLRP11 is required for full recognition of mycobacteria by each of these pathways. Our work extends the spectrum of bacterial pathogen recognition by the non-canonical NLRP11-caspase4/caspase-5 pathway beyond gram-negative bacteria.IMPORTANCEThe activation of inflammasome complexes plays a crucial role in intracellular pathogen detection. NLRP11 and caspase-4 are essential for recognizing lipopolysaccharide (LPS), a molecule found in gram-negative bacteria such as the human pathogens Shigella spp., which activate both canonical NLRP3 and non-canonical inflammasome pathways. Through a series of deletion mutants, we demonstrate that the NACHT and LRR domains of NLRP11, but not its pyrin domain, are critical for detection of S. flexneri. Notably, our research reveals that the acid-fast bacterium M. tuberculosis is also detected by NLRP11 and caspase-4, despite not producing LPS. These findings significantly expand the range of pathogens recognized by NLRP11 and caspase-4 to now include acid-fast bacteria that do not contain LPS and underscore the versatility of these innate immune components in pathogen detection.